Twelve Questions for the Participatory Modeling Community. Issue 8 (3rd August 2018) - Jordan, Rebecca; Gray, Steven; Zellner, Moira; Glynn, Pierre D.; Voinov, Alexey; Hedelin, Beatrice; Sterling, Eleanor J.; Leong, Kirsten; Olabisi, Laura Schmitt; Hubacek, Klaus; Bommel, Pierre; BenDor, Todd K.; et al.
Abstract: Participatory modeling engages the implicit and explicit knowledge of stakeholders to create formalized and shared representations of reality and has evolved into a field of study as well as a practice. Participatory modeling researchers and practitioners who focus specifically on environmental resources met at the National Socio‐Environmental Synthesis Center (SESYNC) in Annapolis, Maryland, over the course of 2 years to discuss the state of the field and future directions for participatory modeling. What follows is a description of 12 overarching groups of questions that could guide future inquiry. Key Points: Reported are future directions in participatory modeling as decided by a group of experts This paper discusses broad questions of practice, participation, and innovation that can be addressed by researchers from many fields